Praktikalitas Modul Asam Basa Berbasis Inkuiri Terbimbing Kelas XI MIPA - Mutia Shafitri; Iryani Iryani (Edukimia, 2021)
This study aims to determine the practicality of the guided inquiry-based acid-base module in class XI MIPA. This study uses a plomp development model consisting of 3 stages, namely initial research, prototype development, and the assessment stage. The instrument used in the practicality test is in the form of a questionnaire given to teachers and students. The practicality value is calculated by using Aiken V formula. The result of this study indicates that the module developed has a practical value of 0,89 with a high category.